Aktivitas Menggigit Nyamuk Aedes spp di Tiban Baru, Kota Batam: The Mosquito Biting Activity of Aedes spp in Tiban Baru, Batam City - Kurnia, Risman; Novalia, Rusnaini; Daswito, Rinaldi; Gunnara, Harvensica (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2023)
Tiban Baru area is one of the endemic areas of Dengue Fever (DHF) in Batam City. Previous studies have reported nocturnal blood-sucking activities of Aedes spp mosquitoes in several regions in Indonesia. The behavioral change of the blood-sucking activity of Aedes spp mosquitoes may impact the transmission of dengue fever. The study aimed to determine the activity of Aedes spp, a vector of DHF in the Tiban Baru area, Batam City. The research was descriptive with a cross-sectional design. This study was conducted in 25 houses, with mosquito collection in the field using the resting mosquito collection method starting from 6:00 pm to 6:00 am.  Measurement of environmental parameters including temperature and humidity in the environment around the study.  The results stated that there was a change in the blood-sucking activity of Aedes spp mosquitoes from 16.00 to 17.00 to 18.00 to 21.00. The distribution of Aedes albopictus mosquitoes in the Tiban Baru area was 89.4% of the total Aedes spp mosquitoes collected with a Man Bitting Rate (MBR) value of 56.6%. The average temperature and humidity in the Tiban Baru area were 280C and 75%. Changes in the blood-sucking activity of Aedes spp mosquitoes can increase the risk of dengue transmission so efforts are needed for the prevention and control of dengue vectors in the study area.